Analisis Sistem Pertumbuhan dan Sintasan Ikan Kakap, Kerang Hijau dan Anggur Laut Pada Budidaya Terintegrasi Sistem Resirkulasi Terkontrol - Lusiana Lusiana; Heriansah Heriansah; Arnold Kabangnga; Nur Annisa Firliana Muchlis; Muh. Imanuddin Akmal (Jurnal Riset Diwa Bahari (JRDB), 2025)
Integrated aquaculture or IMTA is a cultivation method that involves several communities with different trophic levels, in terms of the utilization of food sources (energy) in the waters. To determine the effect of species combinations on snapper growth in integrated cultivation of controlled recirculation system and To determine the effect of species combination on snapper survival in integrated cultivation of controlled recirculation system, the research method used was Complete Random Design (RAL) with 4 treatments and 3 replications and used ANOVA (Analysis Of Variance) data. The results showed that the survival of white snapper during 5 weeks of maintenance showed that the cultivation system had a significant effect on the ability of fish to survive, with the highest value in P4 treatment (IMTA) of 85.0% and lowest in P1 treatment (monoculture) of 43.80%, while P2 and P3 treatment reached 54.20% and 60.40% respectively. This pattern indicates that the integration of snapper with green shellfish and sea grapes in the IMTA system is able to create a more stable maintenance environment and support fish survival through the use of feed waste and feces as a source of nutrition for other organisms, thereby reducing the accumulation of toxic materials such as ammonia that have the potential to trigger stress and death. The results of ANOVA's analysis, which showed a significant influence of species combinations on synthesizers, as well as Tukey's follow-up tests, which confirmed the very real difference between P4 and other treatments, reinforced that integrated aquaculture approaches are more effective than monocultures or simple polycultures in improving the survival of white snapper in a closed recirculation system